Types of dynamics of the state of meliorated agrolandscapes - D. A. Ivanov (Аграрная наука Евро-Северо-Востока)
The paper describes the main types of spatial and temporal variability of natural geosystems and agrolandscapes components under the influence of natural causes and anthropogenic factors. Features of long-term dynamics of climate condition, the lithologic base, a relief, natural waters, soils and vegetation within natural geosystems and agrolandscapes are revealed. The regulations on the adaptive reactions of geocomplexes components to external and internal factors of variability of natural environment has been determined. It is shown that these reactions are the driving force of landscape genesis of natural territorial complexes and agrogeosystems. The main thesis of the work is the statement about the secondary role of human activity in the process of landscape genesis of anthropogenic landscapes, including agrogeosystems. Anthropogenic impact only modifies the pattern of natural landscape processes. It is shown that the characteristics of the derivative components of the landscape - natural waters, soils and vegetation - are the most dynamic. The anthropogenic dynamics of the state of these natural bodies is rather complex and multifaceted. The most fully described are adaptive reactions of soil cover and vegetation of natural landscapes and anthropogenic geosystems. The dependence of the state of the landscape soil cover upon the trends of the evolutionary dynamics of climate and terrain are revealed. The paper focuses on the influence of meliorative actions on a condition of soil fertility and soil cover structure. The types of plant successions and their relationship with the dynamics of soil cover are described in detail. The theoretical description of features of functioning of the natural, anthropogenically transformed and reclaimed landscape which is mostly changed, gives the chance of creation the technologies of landscape engineering that is the system of management the natural environment parameters of soil used for agriculture.